Selective binding of bacterial toxins to major histocompatibility complex class II-expressing cells is controlled by invariant chain and HLA-DM - Lavoie, Pascal M. (The National Academy of Sciences of the USA, 1997)
Bacterial superantigens (SAgs) bind to major histocompatibility complex (MHC) class II molecules and activate T cells in a Vβ-restricted fashion. We recently identified subsets of HLA-DR1 molecules that show selectivity for SAgs. Here, we extend these observations by showing that different cell lineages demonstrate distinct SAg-binding specificities although they all express HLA-DR1. Indeed, B cells bind staphylococcal enterotoxin A (SEA) and toxic shock syndrome toxin 1 (TSST-1) with high affinity while staphylococcal enterotoxin B (SEB) binding is barely detectable. In contrast, DR1-transfected HeLa cells show efficient binding of SEB, but not of SEA or TSST-1. We investigated the class II maturation events required for efficient interaction with SAgs and found that the ability of cells to bind and present the toxins can be drastically modulated by coexpression of the class II-associated invariant chain (Ii) and HLA-DM. SEA binding to DR1 molecules required coexpression of Ii, whereas TSST-1 binding was selectively enhanced by DM. Binding of SEB was affected by cell type-specific factors other than Ii or DM. The selectivity of SAgs for different MHC class II populations was minimally affected by HLA-DR intrinsic polymorphism and could not be explained by binding to alternative sites on DR molecules. Our results indicate that SAgs are sensitive to structural heterogeneity in class II molecules, which is consequent to the differential regulation of expression of antigen processing cofactors. Therefore, we speculate that Staphylococcus aureus have retained the ability to express numerous SAgs in adaptation to the micro-heterogeneity displayed by MHC class II molecules and that this may relate to their ability to infect different tissues.